FLR 2018
DOI: 10.14786/flr.v6i3.353
|View full text |Cite
|
Sign up to set email alerts
|

Using sensor technology to capture the structure and content of team interactions in medical emergency teams during stressful moments

Abstract: In healthcare, action teams are carrying out complex medical procedures in intense and unpredictable situations to save lives. Previous research has shown that efficient communication, high-quality coordination, and coping with stress are particularly essential for high performance. However, precisely and objectively capturing these team interactions during stressful moments remains a challenge. In this study, we used a multimodal design to capture the structure and content of team interactions of medical team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Our application of the variability thesis to leadership research illuminates the importance of this gripe (Navarro & Rueff-Lopes, 2015). By pairing a microbehavioral approach with measuring the continuous physiological data of leaders at the intra-individual level, we are able to answer an essential "when" type of question (see also Endedijk, Hoogeboom, Groenier, de Laat, & Van Sas, 2018). Highly effective leaders are especially likely to show variability in their physiological response "when" they display (both positive and negative) relations-oriented behaviors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Our application of the variability thesis to leadership research illuminates the importance of this gripe (Navarro & Rueff-Lopes, 2015). By pairing a microbehavioral approach with measuring the continuous physiological data of leaders at the intra-individual level, we are able to answer an essential "when" type of question (see also Endedijk, Hoogeboom, Groenier, de Laat, & Van Sas, 2018). Highly effective leaders are especially likely to show variability in their physiological response "when" they display (both positive and negative) relations-oriented behaviors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Teams may, indeed, tailor their interactions to the nature of the work at hand: Complex team tasks may require complex interactions among the team members. Thus, to explain why teams are effective, we must incorporate both the nonlinear nature of team interaction patterns and the contexts in which such patterns occur (Endedijk, Hoogeboom, Groenier, de Laat, & Van Sas, 2018; Kerr, 2017; Marks, Mathieu, & Zaccaro, 2001; Mathieu et al, 2019; Pentland, 1992; Ramos-Villagrasa, Marques-Quinteiro, Navarro, & Rico, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown effects of, for example, team familiarity on team communication and adaption to change, (Muskat et al, 2022), the desired balance between the size of a team and the information processing demands in relation to team learning behaviors (Staats et al, 2012;Wiese et al, 2022), and that teams with a formal leader show different (amounts of) team learning behaviors compared to leaderless teams such as the teams included in the current study (Wiese et al, 2022). Although the number of teams was limited, we know from research on different team processes that variation within teams is often larger than variation between teams (Endedijk et al, 2019). Therefore, observing complete lifespans of six different teams, covering a total of 100 meetings, has provided us with a very comprehensive set of data that allowed us to capture a great deal of variations in team reflexivity.…”
Section: Limitations and Future Studiesmentioning
confidence: 93%